Phase shift reflectometry for wafer inspection - Peng, Kuang (2018)
In 3D measurement, specular surfaces can be reconstructed by phase shift reflectometry and the system configuration is simple. In this paper, a wafer is measured for industrial inspection to make sure the quality of the wafer by calibrating, phase unwrapping, slope calculation and integration. The profile result of the whole wafer can be reconstructed and it is a curve. As the height of the structures on the wafer is the target we are interested in, by fitting and subtracting the curve surface, the structures on the wafer can be observed on the flat surface. To confirm the quality farther, a part of the wafer is captured and zoomed in to be detected so that the difference between two structures can be observed better.